STRATEGI PEMASARAN ONLINE PRODUK SAMBAL GORENG IKAN TERI DAPUR FIZZUL DALAM MEMPERLUAS PASAR - Sabela Kirana Widyadhana; Ni Made Ida Pratiwi (Cahaya Ilmu Bangsa, 2024)
Online marketing has become a vital tool for businesses to reach a wider customer base beyond geographical limitations. This applies not only to larger corporations but also to small and medium-sized businesses (SMBs). To expand their market, SMBs need to have an effective internet marketing plan in place. Strategies such as leveraging product-related information and utilizing social media platforms can significantly enhance product visibility. Additionally, employing digital marketing techniques like search engine optimization (SEO), social media marketing, and influencer marketing can help target more niche audiences. By implementing these strategies, a company like Dapur Fizzul can increase sales and expand their market for their Sambal Goreng Ikan Teri product. Utilizing the power of online marketing is essential for businesses seeking growth and increased exposure in today's digital landscape.